Representational Competence in Science Learning: A Systematic Review - Arifiyanti, Fitria; Pásztor, Attila (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2025)
Representational competence is one of the essential competence to learn science concepts. When students achieve high representational competence, they can begin to transform external representations into internal representations, which improves performance on visual tasks, memory tasks, and cognitive problem-solving in science learning. Although the theoretical effectiveness of representational competence in science learning is well-established, empirical evidence remains limited, and findings are inconsistent. This systematic review aims to examine studies investigating representational competence across various characteristics, including science fields, countries, participants, topics, and assessment methods. Out of 211 records, 67 studies were selected for qualitative assessment. The results reveal that representational competence has been studied in diverse contexts, with a range of assessments used to evaluate students’ competence in science. However, further research is needed to identify the factors influencing students' representational competence and their impact on learning achievement in science.